Efektifitas Lembaga Bipartit Dalam Menyelesaikan Sengketa Hubungan Industrial Pada Perusahaan Pt. New Kuta Golf And Ocean View - I Nyoman Putu Budiartha; I Putu Gede Seputra; Dynna Madina Karuniawan (Jurnal Konstruksi Hukum, 2020)
The increasingly important demands of industrialization for the progress a country have consequences for employers to use effective systems wherever possible. However, industrial disputes between workers and employers are often a problem. Therefore we need a set of laws that can be a separate forum for dealing with dispute matters within a company, is Bipartite Cooperative. The problem raised in this paper is how the effectiveness of the Bipartite Institute and what are the things that hamper in resolving employment issues at PT New Kuta Golf and Ocean View. The research method used is an empirical legal research method through the sociology of law approach. The results obtained, that is about disputes that have occurred in the company namely working conditions, requirements of work, increased work productivity and welfare of workers who impact on the company. The form of settlement is done through Bipartite and termination of employment. The inhibiting factors found were weak mindset, limited information, lack of competent human resources towards understanding Bipartite.